Potassium Titanyl Phosphate Laser Turbinate Reduction in the Management of Allergic Inferior Turbinate Hypertrophy: Our Experience. Issue 1 (March 2016) - Vijayakumar, Sabarinath; Divakaran, Shilpa; Parida, Pradipta Kumar; Gopalakrishnan, Suriyanarayanan
Background: Allergic inferior turbinate hypertrophy is one of the most common causes of nasal obstruction. Several surgical methods can be used for the reduction of allergic inferior turbinate hypertrophy refractory to medical management. Herein, we share our experience with a potassium titanyl phosphate (KTP) laser, which is a relatively novel technique for turbinate reduction. Objectives: To evaluate the efficacy of KTP laser turbinate reduction in terms of symptomatic improvement and its effect on nasal mucociliary clearance. Methods: This study was conducted in the Jawaharlal Institute of Postgraduate Medical Education and Research, Puducherry, India, from November 2012 to July 2013. Thirty patients with inferior turbinate hypertrophy refractory to medical management were selected. A KTP laser was used at 6 W in continuous mode, with a spot size of 0.6–1 mm, and energy delivered through a 400–μm optical fiber. A follow-up was done at 1 week, 1 month, and 3 months. All the values (both by the Sino Nasal Outcome Test scoring system and saccharine transit time) were assessed before surgery and at each follow-up visit. Results: The patients showed significant differences in the symptoms (p < 0.0001) at each follow-up. The mean saccharin transit time showed significant prolongation during the first week and first month after surgery, which indicated adverse effects on the mucociliary system (p < 0.0001). This, however, was a temporary effect, and the mean saccharin time returned to normal limits (17.96 minutes) at the third postoperative month. The mean operative time was 11.62 minutes. The procedure was not associated with any serious intra- or postoperative complications. Conclusion: KTP laser turbinate reduction is a safe, effective, and minimally invasive procedure in the treatment of allergic inferior turbinate hypertrophy, with a minimal effect on the nasal mucosa. It can be done as an office procedure, with minimal complications.